1998
DOI: 10.1093/humupd/4.5.472
|View full text |Cite
|
Sign up to set email alerts
|

Marker genes of decidualization: activation of the decidual prolactin gene

Abstract: Decidualization of human endometrial stromal (ES) cells in vitro is induced by cAMP analogues and ligands that elevate cellular cAMP levels in a manner resembling the gonadotrophins, prostaglandin E2 and relaxin (RLX). This differentiation process is marked by the onset of decidual prolactin (PRL) production in the late luteal phase of the cycle. Using transfection assays and a primary ES cell culture system, we have demonstrated that decidual PRL gene transcription is driven by an alternative upstream promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 40 publications
3
83
0
2
Order By: Relevance
“…We then showed that suppression of stathmin Thus, our study supports previous observations suggesting that stathmin may be involved in the proliferation and/ or differentiation of primary endometrial cells in humans [16]. Ovarian steroids induce endometrial stromal cell differentiation by activating the cAMP pathways and stromal cells that are freshly isolated from normal endometrial tissues decidualize when treated with either progesterone plus estradiol or db-cAMP [15]. In fact, several endometrial cell lines respond to steroid treatment [20]; however, the EtsT cell line does not decidualize upon treatment with progesterone plus estradiol (data not shown).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We then showed that suppression of stathmin Thus, our study supports previous observations suggesting that stathmin may be involved in the proliferation and/ or differentiation of primary endometrial cells in humans [16]. Ovarian steroids induce endometrial stromal cell differentiation by activating the cAMP pathways and stromal cells that are freshly isolated from normal endometrial tissues decidualize when treated with either progesterone plus estradiol or db-cAMP [15]. In fact, several endometrial cell lines respond to steroid treatment [20]; however, the EtsT cell line does not decidualize upon treatment with progesterone plus estradiol (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…These types of studies have shown that when uterine endometrial stromal cells transform into decidualized stromal cells, they are altered morphologically and begin to secrete specific decidual proteins [14]. In vitro studies have also shown that stromal cell preparations decidualize when exposed to ovarian steroids (progesterone and estradiol) or agents that activate the cAMP pathway [15]. In our previous report, we also used primary endometrial stromal cell cultures to explore the role of stathmin in decidualization.…”
mentioning
confidence: 99%
“…A persistent elevation of intracellular cAMP in stromal cells is essential for acquisition and maintenance of the decidual phenotype. 1,43 In the late secretory phase of the menstrual cycle, endometrial stromal cells are exposed to a variety of local and endocrine factors that bind to G-protein coupled receptors and stimulate the production of cAMP, including prostaglandin E 2 , relaxin, corticotropin-releasing hormone, and the gonadotropins luteinizing hormone and follicle stimulating hormone. 1 In pregnancy, the decidua is exposed to vast amounts of human chorionic gonadotropin (hCG) secreted by the syncytiotrophoblast, and signaling through the luteinizing hormone/hCG receptor involves cAMP as a second messenger.…”
Section: Discussionmentioning
confidence: 99%
“…(Data derived from Wang et al, 1998. ) cAMP−protein kinase A signalling pathway (reviewed in Telgmann and Gellersen, 1998). cAMP alone can induce prolactin production in endometrial monolayers and this effect is synergistically enhanced by medroxyprogesterone acetate (Brosens et al, 1999).…”
Section: Prolactin Expression In the Decidualized Endometrium And Itsmentioning
confidence: 99%